Evaluating the performance of the search and matching model - Eran Yashiv (Institute for the Study of Labor (IZA), 2006)
Does the search and matching model fit aggregate U.S. labor market data? While the model has become an important tool of macroeconomic analysis, recent literature pointed to some significant failures in accounting for the data. This paper aims to answer two questions: (i) Does the model fit the data, and, if so, on what dimensions? (ii) Does the data fit the model, i.e. what are the data which are relevant to be explained by the model? The analysis shows that the model fits certain specifications of the data on many dimensions, though not on all. This includes capturing the high persistence and high volatility of most of the key variables, the negative co-variation of unemployment and vacancies, and the behavior of the worker job finding rate. A key role in this fit is played by the convexity of hiring costs and the stochastic properties of the separation rate. The latter is a major component of the rate discounting the future value of the job-worker match. The paper offers a workable, empirically-grounded version of the model for the analysis of aggregate U.S. labor market dynamics.
Keywords: E24; E32; J32; J63; 330; search; matching; U.S. labor market; vacancies; labor market flows; business cycles; Arbeitsplatzsuchmodell; Arbeitsmarkt; USA